Heterogeneous brand identities in Cross-IP mobile game collaborations: a case study of visual design characteristics - Annisa, Naira Pelangi; Rahman, Yanuar; Swasty, Wirania (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
The rise of mobile games has opened a new potential market for brands, but there is a lack of research focusing on mobile game collaboration designs, as they tend to focus on other industries despite the mobile game industry having a high rate of collaborations. The objective of this study is to extend the subject of brand collaboration design analysis into the mobile gaming landscape. In addition, we will analyze how mobile game collaborations incorporate brand identity extensions of heterogeneous visual identities into distinctive designs, and the rationale of how these collaborations work well despite the contrasting brand identities. To analyze, we used a qualitative case study method. The case study includes three cases of mobile game collaborations chosen based on heterogeneity, originality, and utilization. The main findings of this paper are the design characteristics of the collaborative product, which consists of six attributes. This study can be used as a reference for the key design characteristics in heterogeneous mobile game collaboration designs in the future.